Evaluation of different clean heat supply modes based on crop straws in the rural area of Northern China - Huo, Lili; Yao, Zonglu; Jia, Jixiu; Zhao, Lixin; Cong, Hongbin; Meng, Haibo; Yuan, Yanwen (International Journal of Agricultural and Biological Engineering, 2020)
This study evaluated eight different types of heat supply modes based on crop residues utilization in the rural area of Northern China, including straw densified solid fuel combustion, pyrolysis char combustion, biogas combustion, and pyrolysis gas combustion for single household heating; straw densified solid fuel combustion, baling straw combustion, biogas combustion, and pyrolysis gas combustion for centralized heating; centralized gas supply and centralized pyrolysis gas supply modes. Comprehensively evaluation was the cost of these different eight heat supply modes. The results showed that the cost of straw densified solid fuel combustion, pyrolysis char combustion for single household heating were 2346 RMB/household and 2390 RMB/household. With the heating scale of 200-500 households, the pipe network distance was 8 m/household, and the total annual heating cost was predicted at 2201-2992 RMB/household. Among them, the cost of straw baling combustion for centralized heating was the lowest, the cost of densified solid fuel, biogas, and pyrolysis for centralized heating was the second, and the cost of biogas and pyrolysis gas for centralized gas supply was the highest. For the increase in every 1 m of the pipeline distance, the investment cost will increase by about 645 RMB for each household. This study provides a basis for the implementation of clean heat supply technologies in less-developed areas and guidance of village heat-supply subsidy policies.Keywords: crop straw, biomass, clean heating, rural area, villages and towns, model, costDOI: 10.25165/j.ijabe.20201305.5600Citation: Huo L L, Yao Z L, Jia J X, Zhao L X, Cong H B, Meng H B, et al. Evaluation of different clean heat supply modes based on crop straws in the rural area of Northern China. Int J Agric & Biol Eng, 2020; 13(5): 209–217.